Tithonia spells trouble for termites - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Farmers working with the Kenya Woodfuel and Agroforestry Programme (KWAP) have identified a local shrub as having potential to help control termite infestations. Farmers, involved in the project as part of a 'participatory rural appraisal' approach...